(untitled) (Journal of Oriental Studies, 2016)
This text considers the sympathy and antipathy to the numbers in Kazakh, Russian and Chinese nations and the reasons for their formation. A special feature of this paper is that the number in the Kazakh, Russian and Chinese cultures exhibit universality and nationality under the influence of different factors. Only awareness of differences in culture properties of these peoples, the people who study these languages will be able to overcome the barrier in intercultural communication, enhance mutual communication and increase cultural exchanges.